Colon diverticulosis is not a risk factor for the detection of adenomatous polyps – results of a prospective study - Poszler, Alexander; Walter, Benjamin; Aulehner-Forlenza, Christina; Haller, Bernhard; Abdelhafez, Mohamed; Brown, Hayley; von Delius, Stefan; Born, Peter; Schmid, Roland M.; Bajbouj, Monther; Klare, Peter (Zeitschrift für Gastroenterologie, 2020)
Background and aims Colon diverticula (CD) and adenomatous polyps are frequently found during colonoscopy. Data from the literature contains inconsistent information about whether patients with CD have a higher risk for colon adenomas. A positive correlation might influence the current guidelines for screening colonoscopies. The aim of this study was to examine whether presence of CD is associated with endoscopic adenoma detection.Materials and methods This was a prospective study at 2 centers in Germany. Patients with an indication for colonoscopy were included. The number and localization of diverticula were recorded. Detected polyps were resected, and histopathological results were captured. Logistic regression models were fitted to the data to evaluate the association between CD and adenoma detection.Results A total of 938 colonoscopies was included. CD occurred in 49.1 % of the colonoscopies. The polyp and adenoma detection rates (PDR, ADR) were 50.3 % and 32.3 %. In 37.5 % of the patients with diverticula, at least 1 adenoma was detected, whereas this was the case in 27.3 % in the absence of diverticula. The presence of diverticula was positively correlated with the detection of adenomas in univariate analysis (p = 0.001), but no significant association could be found in multivariable analysis (p = 0.775). Increasing age (p < 0.001), male sex (p = 0.005), and longer withdrawal time (p < 0.001) were significant predictors for adenoma detection in the multivariable analysis. Similar results were also observed for both the distal and the proximal colon.Discussion Diverticula and adenomas are frequently found during colonoscopies. However, diverticula disease was not significantly associated with adenoma detection after adjustment for relevant prognostic factors. Older age, male sex, and duration of withdrawal time are predictors for the detection of adenomatous polyps.
Keywords: diverticulum; colon adenoma; adenoma detection rate; colonoscopy; endoscopy